Nano-porous high-entropy alloy for composite binder grinding wheel and preparation method and application of nano-porous high-entropy alloy
By using a nanoporous high-entropy alloy composed of Ti-Co-Ni-Sn as the grinding wheel binder matrix, the problems of low efficiency and high damage layer of traditional grinding wheels when grinding large-sized hard and brittle materials are solved, achieving the effects of high-efficiency grinding and high yield.
Patent Information
- Application Number
- CN202510806619.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-09-23
AI Technical Summary
When grinding large-sized hard and brittle materials, traditional resin-metal composite bond grinding wheels have low grinding efficiency, the damage layer cannot be further reduced, the yield rate is difficult to improve, and they cannot meet the processing requirements of high-end products.
A nanoporous high-entropy alloy composed of Ti-Co-Ni-Sn is used as the grinding wheel bond matrix. A nanoporous structure is generated by dealloying Fe-Ti-Co-Ni-Sn alloy to improve the abrasive holding force and shape retention of the grinding wheel.
It significantly improves the sharpness and grinding quality of the grinding wheel, reduces the grinding damage layer, and improves the grinding efficiency and yield of hard and brittle materials.
Smart Images

Figure CN120683414A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of abrasive materials and grinding tools, and particularly relates to a nanoporous high-entropy alloy for a composite bond grinding wheel, a preparation method thereof, and an application thereof. Background Art
[0002] Diamond grinding wheels are the primary tool for grinding hard and brittle materials such as cemented carbide, cermets, and semiconductor materials. In recent years, superhard grinding wheels for grinding hard and brittle materials have undergone a transition from single-bond grinding wheels to composite-bond grinding wheels. Resin-metal composite-bond grinding wheels, which combine the sharpness of resin-bond grinding wheels with the wear resistance of metal-bond grinding wheels, have become the primary tool for grinding hard and brittle materials.
[0003] However, as technology has advanced, the size of hard and brittle material blanks has become larger and larger, and processing requirements have become increasingly demanding. Traditional resin-metal composite bond grinding wheels have begun to show their shortcomings when grinding large workpieces. Grinding efficiency cannot be improved, the damage layer cannot be further reduced, and the yield rate cannot be further improved. Their grinding performance is increasingly unable to meet the grinding processing requirements of the market, especially the grinding processing requirements of high-end products. Therefore, it is necessary to respond to this situation and develop grinding wheels with better sharpness, lower grinding damage layer, and higher yield rate to meet the grinding processing conditions of mid-to-high-end hard and brittle material products and improve the overall technical level of the industry. Summary of the Invention
[0004] Based on this, the present invention aims to provide a nanoporous high-entropy alloy for composite bond grinding wheels. The high-entropy alloy is composed of Ti-Co-Ni-Sn and is a nanoporous alloy whose porous structure is generated by dealloying Fe-Ti-Co-Ni-Sn alloy. The high-entropy alloy can significantly improve the sharpness of the grinding wheel as a grinding wheel bond matrix. The bond has a high abrasive holding force, which can improve the shape retention of the grinding wheel, thereby improving the grinding quality of hard and brittle materials.
[0005] The present invention also provides a method for preparing the nanoporous high entropy alloy for the composite bond grinding wheel.
[0006] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a nanoporous high-entropy alloy for a composite bond grinding wheel, which is characterized by being mainly made of the following raw materials in weight percentage: Fe 10-30wt%, Ti 8-20wt%, Co 8-20wt%, Ni 10-25wt%, and Sn 20-40wt%.
[0007] Furthermore, the preferred weight percentages of the materials are: Fe 12-28wt%, Ti 10-20wt%, Co 9-17wt%, Ni 12-24wt%, and Sn 22-40wt%.
[0008] The present invention further provides a method for preparing a nanoporous high entropy alloy for a composite bond grinding wheel, comprising the following steps: S1, adding Fe, Ti, Co, Ni, and Sn powders in proportion to each other in a high-frequency resonance mixer, mixing them uniformly, and obtaining a mixture after sieving; S2, sintering the mixed material to obtain a Fe-Ti-Co-Ni-Sn alloy block; S3, first remove the surface oxide layer of the Fe-Ti-Co-Ni-Sn alloy block, then place it in an excess of tartaric acid solution to react and remove Fe, then take it out, wash it, and dry it to obtain a Ti-Co-Ni-Sn nanoporous high entropy alloy.
[0009] Furthermore, the Malvern particle size D50 of each elemental powder in S1 is less than 10 μm, the mixing time is 30 to 45 minutes, and the screening process is: passing through a 325-mesh sieve 4 to 6 times.
[0010] Furthermore, the preferred Malvern particle size D50 of the Fe powder is 3-6 μm, and the optimal Malvern particle size D50 of other metal element powders is 4-8 μm.
[0011] Furthermore, the temperature rise curve of S2 sintering is: from 25±5°C to 250±50°C after 5±1 minutes, from 250±50°C to 350±50°C after 10±1 minutes, kept at 350±50°C for 10~32 minutes, from 350±50°C to 750±50°C after 100±5 minutes, kept at 750±50°C for 30~55 minutes, cooled to 200±50°C, and then demolded to take out the Fe-Ti-Co-Ni-Sn alloy block.
[0012] Furthermore, the tartaric acid solution in S3 is prepared by mixing tartaric acid powder and deionized water at a mass ratio of 1-10:90-99 until the tartaric acid powder is completely dissolved. Preferably, the mixture of tartaric acid powder and deionized water is heated to accelerate the dissolution of the tartaric acid powder. Furthermore, in S3, a sandblaster is used to remove the oxide layer on the surface of the alloy block; when the tartaric acid solution reacts with the alloy block to remove Fe atoms in the alloy block, the reaction is accelerated in a 100° C. water bath ultrasonic machine until no bubbles appear on the surface of the grinding wheel block, heating is stopped, and the alloy block is removed.
[0013] Furthermore, the cleaning in S3 is: using deionized water to ultrasonically clean the alloy block for 10 to 30 minutes, during which the water is changed 3 to 5 times; and the drying is: drying at 60 to 90° C. for 1 to 3 hours.
[0014] The present invention further provides a nanoporous high entropy alloy for composite bond grinding wheels prepared by the above preparation method.
[0015] Furthermore, the composite bond grinding wheel uses a nanoporous high-entropy alloy, and the high-entropy alloy is composed of Ti-Co-Ni-Sn, with a melting point of 320°C~550°C, a flexural strength of 110~145Mpa, a pore size of 620~3500nm, and a porosity of 25~55vol%; preferably, the melting point of the high-entropy alloy is 380°C~500°C, and the flexural strength is 115~135Mpa.
[0016] The present invention further provides an application of the nanoporous high entropy alloy for composite bond grinding wheels in the preparation of composite bond grinding wheels.
[0017] The present invention further provides a composite bond grinding wheel containing the nanoporous high entropy alloy for the composite bond grinding wheel.
[0018] Furthermore, the composite bond grinding wheel comprises, by volume percentage, 18-30 vol% of diamond abrasive, 10-50 vol% of mixed resin, and 25-60 vol% of high entropy alloy.
[0019] Furthermore, in the composite bond grinding wheel, the mixed resin in the grinding wheel is a mixture of polyurethane and polyimide resin, and the volume ratio of the polyurethane to the polyimide resin is 1:2-4.
[0020] The present invention further provides a method for preparing the composite bond grinding wheel, which comprises the following steps: (1) Pour specific weights of diamond, mixed resin, and high entropy alloy into a high-frequency resonance mixer and mix them uniformly according to the required proportion to obtain a mixture; (2) Pour the mixture into the assembled mold cavity, scrape the material, cover the pressure plate, and then put the assembled mold into the hot press to press it into shape with a pressing pressure of 0.15KN / mm 2 ; (3) Demolding and demoulding to obtain the composite bond grinding wheel of the present invention.
[0021] The beneficial effects of the present invention are: 1. The nanoporous high-entropy alloy for composite bond grinding wheels provided by the present invention is composed of Ti-Co-Ni-Sn and is a nanoporous alloy with a pore diameter of 620~3500nm and a porosity of 25~55vol%.
[0022] 2. The nanoporous high-entropy alloy for composite bond grinding wheels provided by this invention has a melting point of 320°C to 550°C, preferably 380°C to 500°C, and a flexural strength of 110 to 145 MPa, preferably 115 to 135 MPa. This material exhibits low melting point, hardness, and brittleness, making it particularly suitable for the formulation of composite bond grinding wheels for grinding hard and brittle materials.
[0023] 3. When the nanoporous high-entropy alloy provided by the present invention is used to prepare a composite bond grinding wheel, the titanium atoms in the alloy, which serves as the grinding wheel bond matrix, are enriched on the surface of the diamond / cubic boron nitride abrasive in the grinding wheel, reacting to form titanium carbide / titanium nitride. This increases the bond's grip on the abrasive, thereby enhancing the sharpness of the grinding wheel. This improves the shape retention of the grinding wheel, thereby enhancing the grinding quality and efficiency of hard and brittle materials, and minimizing damage to the workpiece.
[0024] 4. The present invention provides a method for preparing a nanoporous high-entropy alloy for a composite bond grinding wheel. The dealloying process involves acid etching the alloy block with a tartaric acid solution, which reacts with the trivalent Fe ions in the alloy block to form a complex. As the Fe ions in the alloy block dissolve, the uncorroded metal atoms in the alloy diffuse into each other to form a solid solution. This process continues until all the Fe ions in the alloy are corroded, forming a solid solution and producing a nanoporous high-entropy alloy.
[0025] 5. The present invention provides a method for preparing a nanoporous high-entropy alloy for composite bond grinding wheels. The raw materials vary widely in density, and a high-frequency resonance mixer is used to thoroughly mix the raw materials. All raw materials are elemental metal powders, and the Malvern particle size (D50) is within 10 microns. The Malvern particle size (D50) of Fe powder is 3-6 μm, while the Malvern particle size of other elemental metal powders is optimally 4-8 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Attachment Figure 1 This is a SEM test image of the nanoporous high entropy alloy for composite bond grinding wheels provided by the present invention, with a scale of 20 μm; Attachment Figure 2 This is the XRD test diagram of the nanoporous high-entropy alloy for composite bond grinding wheels provided by the present invention, wherein the upper figure is before treatment with tartaric acid solution, and the lower figure is after treatment with tartaric acid solution. DETAILED DESCRIPTION
[0028] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. The embodiments mentioned are all implemented based on the technical solutions of the present invention, and detailed implementation processes are given. However, it should be noted that the scope of protection of the present invention is not limited to the following embodiments.
[0029] Both "top-down" and "bottom-up" approaches are widely used in the synthesis of nanoscale high-entropy alloys. The key and difficulty in synthesizing nanoscale high-entropy materials lies primarily in the rational selection of elements and their simultaneous reduction through appropriate methods to form a single-phase solid solution structure. The varying melting points, compatibilities, and reduction potentials of individual elements pose significant challenges to the synthesis of high-entropy alloys. Furthermore, a systematic review of the synthesis principles of high-entropy alloys under various environments is essential.
[0030] Example 1 1. A nanoporous high-entropy alloy for composite bond grinding wheels, comprising 28 wt% Fe, 12 wt% Ti, 9 wt% Co, 21 wt% Ni, and 30 wt% Sn. The Fe powder has a Malvern particle size (D50) of 3 μm, and the other metal powders have a Malvern particle size (D50) of 4 to 6 μm.
[0031] 2. The preparation method of the high entropy alloy is: (1) Weigh the individual components of the alloy in the required proportions and add them into a high-frequency resonance mixer for mixing for 30 minutes, then pass through a 325-mesh sieve 5 times; (2) Weigh a certain amount of mixed material and put it into the mold cavity, scrape the material, cover the pressure plate, and place the assembled mold into a vacuum sintering press for pressing; (3) The heating curve of the sintering press is as follows: from room temperature (25±5℃) to 250℃ in 5 minutes, from 250℃ to 350℃ in 10 minutes, kept at 350℃ for 15 minutes, from 350℃ to 750℃ in 100 minutes, kept at 750℃ for 38 minutes, cooled to 200℃, and the alloy block was removed from the mold; (4) Use a sandblaster to remove the oxide layer on the surface of the alloy block, then place the alloy block in a beaker filled with an excess of 3wt% tartaric acid solution, place the beaker in a 100℃ water bath ultrasonic machine to accelerate the reaction, stop heating until no bubbles appear on the surface of the grinding wheel block, and remove the grinding wheel block; (5) The alloy block was ultrasonically cleaned with deionized water for 18 minutes, during which the water was changed three times, and then dried at 65°C for 1.5 hours to obtain the nanoporous high-entropy alloy of the present invention. The pore size was 1000-2500 nm, and the porosity was 45 vol%.
[0032] 3. Prepare the tartaric acid solution by mixing tartaric acid powder and deionized water at a mass ratio of 3:97 until the tartaric acid is fully dissolved. Heat the mixture in a cup of alcohol to accelerate dissolution.
[0033] 4. The nano high entropy alloy prepared in this embodiment has a melting point of 380°C and a flexural strength of 135 MPa. The high entropy alloy of the present invention exhibits low melting point, hardness, and brittleness, and is particularly suitable for the formulation of composite bond grinding wheels for grinding hard and brittle materials.
[0034] 5. Pour 30vol% diamond, 45vol% mixed resin and 25vol% high entropy alloy into a high-frequency resonance mixer and mix them evenly to obtain a mixture. Pour the mixture into the assembled mold cavity, scrape the material, cover the pressure plate, and then put the assembled mold into a hot press to press and form it. The pressing pressure is 0.15KN / mm 2 , demolding and demoulding, the obtained grinding wheel is named "grinding wheel 1".
[0035] Example 2 1. A nanoporous high-entropy alloy for composite bond grinding wheels, comprising 20 wt% Fe, 15 wt% Ti, 12 wt% Co, 18 wt% Ni, and 35 wt% Sn. The Fe powder has a Malvern particle size (D50) of 4 μm, and the other metal powders have a Malvern particle size (D50) of 5 to 8 μm.
[0036] 2. The preparation method of the high entropy alloy is: (1) Weigh the individual components of the alloy in the required proportions and add them into a high-frequency resonance mixer for 40 minutes, then pass through a 325-mesh sieve 5 times; (2) Weigh a certain amount of mixed material and put it into the mold cavity, scrape the material, cover the pressure plate, and place the assembled mold into a vacuum sintering press for pressing; (3) The heating curve of the sintering press is as follows: from room temperature (25±5℃) to 250℃ in 5 minutes, from 250℃ to 350℃ in 10 minutes, kept at 350℃ for 30 minutes, from 350℃ to 750℃ in 100 minutes, kept at 750℃ for 45 minutes, cooled to 200℃, and the alloy block was removed from the mold; (4) Use a sandblaster to remove the oxide layer on the surface of the alloy block, then place the alloy block in a beaker filled with an excess of 5wt% tartaric acid solution, place the beaker in a 100℃ water bath ultrasonic machine to accelerate the reaction, stop heating until no bubbles appear on the surface of the grinding wheel block, and remove the grinding wheel block; (5) The alloy block was ultrasonically cleaned with deionized water for 20 minutes, during which the water was changed four times, and then dried at 80°C for 2 hours to obtain the nanoporous high-entropy alloy of the present invention. The pore size was 2800-3500 nm, and the porosity was 55 vol%.
[0037] 3. Prepare the tartaric acid solution by mixing tartaric acid powder and deionized water at a mass ratio of 5:95 until the tartaric acid is fully dissolved. Heat the mixture in a cup of alcohol to accelerate dissolution.
[0038] 4. The melting point of the high entropy alloy is 420°C, and the flexural strength is 123 MPa. The high entropy alloy of the present invention exhibits low melting point, hardness, and brittleness, making it particularly suitable for the formulation of composite bond grinding wheels for grinding hard and brittle materials.
[0039] 5. Pour 35vol% diamond, 20vol% mixed resin and 45vol% high entropy alloy into a high-frequency resonance mixer and mix them evenly to obtain a mixture. Pour the mixture into the assembled mold cavity, scrape the material, cover the pressure plate, and then put the assembled mold into a hot press to press and form it. The pressing pressure is 0.15KN / mm 2 , demolding and demoulding, the obtained grinding wheel is named "grinding wheel 2".
[0040] Example 3 1. A nanoporous high-entropy alloy for composite bond grinding wheels, comprising 12 wt% Fe, 18 wt% Ti, 15 wt% Co, 15 wt% Ni, and 40 wt% Sn. The Fe powder has a Malvern particle size (D50) of 6 μm, and the other metal powders have a Malvern particle size (D50) of 4 to 6 μm.
[0041] 2. The preparation method of the high entropy alloy is: (1) Weigh the individual components of the alloy in the required proportions and add them into a high-frequency resonance mixer for 45 minutes, then pass through a 325-mesh sieve 5 times; (2) Weigh a certain amount of mixed material and put it into the mold cavity, scrape the material, cover the pressure plate, and place the assembled mold into a vacuum sintering press for pressing; (3) The heating curve of the sintering press is as follows: from room temperature (25±5℃) to 250℃ in 5 minutes, from 250℃ to 350℃ in 10 minutes, kept at 350℃ for 32 minutes, from 350℃ to 750℃ in 100 minutes, kept at 750℃ for 55 minutes, cooled to 200℃, and the alloy block was removed from the mold; (4) Use a sandblaster to remove the oxide layer on the surface of the alloy block, then place the alloy block in a beaker filled with an excess of 10wt% tartaric acid solution, place the beaker in a 100℃ water bath ultrasonic machine to accelerate the reaction, stop heating until no bubbles appear on the surface of the grinding wheel block, and remove the grinding wheel block; (5) The alloy block was ultrasonically cleaned with deionized water for 30 minutes, during which the water was changed five times, and then dried at 90°C for 3 hours to obtain the nanoporous high-entropy alloy of the present invention. The pore size was 620-800 nm, and the porosity was 25 vol%.
[0042] 3. Prepare the tartaric acid solution by mixing tartaric acid powder and deionized water at a mass ratio of 10:90 until the tartaric acid is fully dissolved. Preferably, heat the mixture over a cup of alcohol to accelerate dissolution.
[0043] 4. The melting point of the high entropy alloy is 500°C, and the flexural strength is 115 MPa. The high entropy alloy of the present invention exhibits low melting point, hardness, and brittleness, and is particularly suitable for the formulation of composite bond grinding wheels for grinding hard and brittle materials.
[0044] 5. Pour 25vol% diamond, 15vol% mixed resin and 60vol% high entropy alloy into a high-frequency resonance mixer and mix them evenly to obtain a mixture. Pour the mixture into the assembled mold cavity, scrape the material, cover the pressure plate, and then put the assembled mold into a hot press to press and form it. The pressing pressure is 0.15KN / mm 2 , demoulding and demoulding, the obtained grinding wheel is named "grinding wheel 3" Comparative Example 1 In this comparative example, a composite bond grinding wheel was prepared using the same method as in the present application, without adding high entropy alloy, and the grinding wheel was numbered "Grinding Wheel 4".
[0045] Comparative Example 2 In this comparative example, a composite bond grinding wheel was prepared using the same method as in the present application, and the high entropy alloy in Example 3 was added in an amount of 15 vol%. The prepared grinding wheel was numbered "Grinding Wheel 5".
[0046] Comparative Example 3 In this comparative example, a composite bond grinding wheel for grooving metal ceramic bars was purchased, numbered "Grinding Wheel 6". Four types of grinding wheels from the above embodiments and comparative examples were used to grind 8-inch silicon carbide wafers on a disco 8540. The feed rate, grinding current, and average depth of the damaged layer on the wafer surface after grinding 10 wafers were recorded, and the results are statistically recorded in Table 1.
[0047] The above results show that when a suitable proportion of high-entropy alloy is added, the composite bond grinding wheel achieves a large feed rate, low current, and shallow damage layer when grinding silicon carbide. However, when no high-entropy alloy is added, or too little high-entropy alloy is added, the feed rate is small, the current is high, the average damage layer is deep, and the yield rate is low when grinding silicon carbide wafers.
[0048] Two of the grinding wheels described in the above embodiments and comparative examples were used to groove a 6 mm diameter metal ceramic bar on a five-axis CNC grinding machine. The single feed amount, feed speed, and bar edge chipping size were recorded, and the results are summarized in Table 2.
[0049] The above results show that, with the addition of a suitable proportion of high-entropy alloy, the composite bond grinding wheel can achieve a large depth of cut and fast feed when grinding cermets, and the workpiece edge is less chipped after grinding. In contrast, conventional grinding wheels available on the market have a low feed rate and are prone to large chipping of the workpiece edge after grinding when grinding cermets.
[0050] The morphology and composition of the nanoporous high entropy alloy for composite bond grinding wheel prepared in the embodiment of the present invention were characterized. Taking Example 1 as an example, the test results are as follows: Figure 1 and Figure 2 shown. Figure 1 The SEM test image of the high entropy alloy shows that the high entropy alloy is a nanoporous alloy with a pore size of 1000~2500nm; Figure 2 This is the XRD test diagram of the high entropy alloy. It can be seen from the figure that after tartaric acid treatment, the Fe in the alloy is completely dissolved, leaving only the FCC phase and α phase.
[0051] In summary, the grinding wheel containing the high entropy alloy of the present invention can achieve large feed, low current, and low loss grinding. This is mainly because the high entropy alloy of the present invention corrodes the metal element Fe during the preparation process. After the Fe atoms are corroded, other metal atoms will undergo reorganization and solid solution. During the reorganization and solid solution process, nano-sized micropores will be formed in the alloy. Combined with the alloy phase formed by the solid solution of other metal atoms, the entire alloy has a low melting point and is brittle. Adding this alloy to the grinding wheel will improve the sharpness of the grinding wheel and reduce the hardness of the grinding wheel, thereby achieving large feed grinding, reducing the depth of the damaged layer of the grinding workpiece, and improving the grinding quality.
[0052] The above description of the disclosed embodiments will enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein, but is to be construed in the widest manner consistent with the principles and novel features disclosed herein.
Claims
1. A nanoporous high entropy alloy for composite bond grinding wheel, characterized in that: It is mainly made of the following raw materials in weight percentage: Fe 10-30wt%, Ti 8-20wt%, Co 8-20wt%, Ni 10-25wt%, and Sn 20-40wt%.
2. A method for preparing a nanoporous high entropy alloy for a composite bond grinding wheel, characterized in that: The steps include: S1, adding Fe, Ti, Co, Ni, and Sn powders in proportion to each other in a high-frequency resonance mixer, mixing them uniformly, and obtaining a mixture after sieving; S2, sintering the mixed material to obtain a Fe-Ti-Co-Ni-Sn alloy block; S3, first remove the surface oxide layer of the Fe-Ti-Co-Ni-Sn alloy block, then place it in an excess of tartaric acid solution to react and remove Fe, then take out the alloy block, wash and dry it to obtain a Ti-Co-Ni-Sn nanoporous high entropy alloy.
3. The preparation method according to claim 2, wherein The particle size D50 of each elemental powder in S1 is less than 10 μm, and the screening process is: passing through a 325-mesh sieve 4 to 6 times.
4. The preparation method according to claim 2, wherein The heating curve of sintering in S2 is as follows: from 25±5°C to 250±50°C in 5±1 minutes, from 250±50°C to 350±50°C in 10±1 minutes, kept at 350±50°C for 10~32 minutes, from 350±50°C to 750±50°C in 100±5 minutes, kept at 750±50°C for 30~55 minutes, cooled to 200±50°C, and then the mold was removed to take out the Fe-Ti-Co-Ni-Sn alloy block.
5. The preparation method according to claim 2, wherein The tartaric acid solution in S3 is prepared by mixing tartaric acid powder and deionized water at a mass ratio of 1-10:90-99 until the tartaric acid powder is completely dissolved.
6. The preparation method according to claim 2, wherein The cleaning in S3 is as follows: ultrasonically cleaning the alloy block with deionized water for 10 to 30 minutes, during which the water is changed 3 to 5 times; and the drying is as follows: drying at 60 to 90° C. for 1 to 3 hours.
7. A nanoporous high entropy alloy for composite bond grinding wheels prepared by the preparation method according to any one of claims 2 to 6.
8. Use of the nanoporous high entropy alloy for composite bond grinding wheels according to claim 7 in the preparation of composite bond grinding wheels.
9. A composite bond grinding wheel comprising the nanoporous high entropy alloy for composite bond grinding wheels according to claim 7.
10. The composite bond grinding wheel according to claim 9, wherein: In terms of volume percentage, the grinding wheel includes 18-30 vol% diamond abrasive, 10-50 vol% mixed resin, and 25-60 vol% high entropy alloy; the mixed resin is a mixture of polyurethane and polyimide resin, and the volume ratio of the polyurethane to the polyimide resin is 1:2-4.